The Relationship between Progression in Axial Length/Corneal Radius of Curvature Ratio and Spherical Equivalent Refractive Error in Myopia - Jong, Monica; Sankaridurg, Padmaja; Naduvilath, Thomas John; Li, Wayne; He, Mingguang (Optometry and vision science, 2018)
This study demonstrates that mean axial length/corneal radius of curvature ratio (AL/CR) can be used to detect low and high myopia but cannot clinically monitor myopia progression because the relationship between AL/CR and progression in myopia is different between low and high myopia. The purpose of this study was to investigate the relationship of AL/CR with magnitude and progression of myopia. Retrospective analysis was conducted comparing the right eyes of those with high myopia (n = 308; age, 7 to 16 years; myopia sphere, -6.00 diopters or worse) with those with low myopia (n = 732; age, 7 to 16 years; myopia sphere, between -0.50 and -3.50 diopters; cylinder, ≤1.00 diopters). Baseline axial length, corneal radii of curvature, and cycloplegic objective refraction were analyzed. Myopia progression in the low-myopia group at 6- and 12-month follow-up was measured, and the differences in slopes of AL/CR were compared for slow (<0.75 diopters) and fast progressing (≥0.75 diopters). Mean AL/CR values were significantly different (P < .001) between high myopia (3.46 ± 0.10) and low myopia (3.16 ± 0.07). In high and low myopia, slopes of axial length versus corneal curvature radius were not significantly different (P > .05), and slopes of AL/CR versus spherical equivalent were significantly different after adjusting for spherical equivalent and age (P < .05). Slopes of AL/CR progression and spherical equivalent progression were significantly different in low myopia between fast and slow progressing (P < .001), but the relationship between progression in AL/CR and progression in spherical equivalent was not strong. The AL/CR can be used to classify different grades of myopia, but it is not useful in determining the magnitude of myopia or monitoring progression because AL/CR is not linearly related to spherical equivalent and because progression in AL/CR is not strongly related to spherical equivalent progression.